Artificial Intelligence and Artistic Creation as Unfolding in Africa - (:unkn) unknown (My University, 2021)
https://thesoleadventurer.com/artificial-intelligence-and-artistic-creation-as-unfolding-in-africa-by-delphine-buysse/
Keywords: African Research